Macula Structure and Microvascular Changes in Recent Small Subcortical Infarct Patients - Cao, Yungang; Yan, Jueyue; Zhan, Zhenxiang; Liang, Yuanbo; Han, Zhao (Frontiers in Neurology, 2021)
Purpose: This study aimed to assess the macula structure and capillaries in the macula and optic nerve head in recent small subcortical infarct (RSSI) patients. Methods: This observational cross-sectional study included 40 RSSI patients and 46 healthy controls. Optical coherence tomography angiography was used to image the capillaries in the macula and optic nerve head. An inbuilt algorithm was used to measure the densities in the microvasculature of the macula [superficial retinal capillary plexus (SRCP) and deep retinal capillary plexus (DRCP)] and optic nerve head [radial peripapillary capillary (RPC)] and thickness around the optic nerve head, peripapillary retinal nerve fiber layer (pRNFL). Results: Densities in RPC (P < 0.001), SRCP (P = 0.001), and DRCP (P = 0.003) were reduced in RSSI patients when compared with healthy controls. The pRNFL thickness was thinner (P < 0.001) in RSSI patients than healthy controls. In the RSSI group, the SRCP density significantly correlated with the DRCP density (rho = 0.381, P = 0.042). The pRNFL thickness displayed a significant relationship with the RPC density (rho = 0.482, P = 0.003) in the RSSI group. Conclusions: RSSI patients showed interrupted capillary plexuses leading to its significant impairment and neurodegeneration. Our report provides insight into the macula capillary microcirculation changes in RSSI.